Imbalance between Fibrin Clot Formation and Fibrinolysis Predicts Cardiovascular Events in Patients with Stable Coronary Artery Disease - Neergaard-Petersen, Søs; Larsen, Sanne B.; Grove, Erik L.; Kristensen, Steen D.; Ajjan, Ramzi A.; Hvas, Anne-Mette (Thrombosis and Haemostasis, 2020)
Background Despite long-term antiplatelet therapy with aspirin, recurrent cardiovascular events remain common in patients with coronary artery disease (CAD).Objective We aimed to determine whether fibrin network characteristics are predictive of vascular events in patients with stable CAD treated with aspirin monotherapy.Methods We included 786 patients with angiographically documented CAD and either prior myocardial infarction, type 2 diabetes mellitus, or both. Median follow-up time was 3 years. At inclusion, fibrin clot properties were evaluated using a turbidimetric assay and the following clot parameters were studied: (1) maximum absorbance, a measure of clot density and fiber thickness; (2) lysis time, assessing fibrinolysis potential; and (3) area under the curve (AUC), a measure of clot formation and lysis. The primary endpoint was the composite of nonfatal myocardial infarction, ischemic stroke, and cardiovascular death. Hazard ratios (HRs) were estimated using multivariable Cox proportional hazards regression.Results A total of 70 primary endpoints occurred. The primary endpoint occurred more frequently in CAD patients with increased clot AUC (crude HR for first vs. fourth quartile: 2.4 [95% confidence interval 1.2–4.6], p = 0.01). This finding remained significant after adjusting for potential confounders (adjusted HR: 2.4 [1.2–4.8], p = 0.01). Neither clot maximum absorbance nor lysis time showed significant association with future vascular events (adjusted HR for maximum absorbance 1.8 [0.9–3.7]; p = 0.09) and lysis time (1.6 [0.8–3.0]; p = 0.18).Conclusion We demonstrate that increased clot AUC predicts future cardiovascular events in stable CAD patients receiving aspirin monotherapy.
Keywords: aspirin; blood coagulation; fibrin clot; fibrinolysis; coronary artery disease